Strain effects on polycrystalline germanium thin films - Toshifumi Imajo; Takashi Suemasu; Kaoru Toko (Scientific Reports, 2021)
Abstract Polycrystalline Ge thin films have attracted increasing attention because their hole mobilities exceed those of single-crystal Si wafers, while the process temperature is low. In this study, we investigate the strain effects on the crystal and electrical properties of polycrystalline Ge layers formed by solid-phase crystallization at 375 °C by modulating the substrate material. The strain of the Ge layers is in the range of approximately 0.5% (tensile) to -0.5% (compressive), which reflects both thermal expansion difference between Ge and substrate and phase transition of Ge from amorphous to crystalline. For both tensile and compressive strains, a large strain provides large crystal grains with sizes of approximately 10 μm owing to growth promotion. The potential barrier height of the grain boundary strongly depends on the strain and its direction. It is increased by tensile strain and decreased by compressive strain. These findings will be useful for the design of Ge-based thin-film devices on various materials for Internet-of-things technologies.